A comparison of fast and slow pyrolysis liquids from mallee. (11th May 2007) - Bridgwater, A.V.; Carson, P.; Coulson, M.
An exploratory comparative study of the fast and slow pyrolysis of eucalyptus mallee has been carried out to explore the differences in liquid yields and characteristics. The study focused on the liquid products, which were fully characterised and good mass balance closures were achieved. The influence of temperature and heating rates on the slow pyrolysis of eucalyptus mallee was investigated, and the results compared to that obtained by fast pyrolysis under orthodox conditions. The advantage of direct liquefaction of biomass is lower cost and higher efficiency transportation of the liquid biofuel to a central user or processing facility.